Edukasi Kemasan Produk sebagai Upaya Meningkatkan Branding dan Daya Tarik Konsumen pada Wirausaha Muda - E, Eyicha; Nurhidayati, Dini; Alisah, Juliah; Yustati, Herlina; Sumarni, Yenti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the competitive digital economy era, product packaging has a strategic role as a visual communication tool that not only protects the product, but also strengthens brand identity and attracts consumer interest. This study aims to examine the effect of packaging education on improving branding strategies and product appeal for young entrepreneurs. Through a qualitative-descriptive approach and literature study, this study explores the packaging education process carried out on MSME actors in Dusun Besar Village, Bengkulu City. The results show that participatory packaging training has succeeded in increasing visual literacy and branding abilities of participants, as indicated by the transformation of packaging design and increased consumer interest in their products. As many as 75% of respondents prefer products with educational packaging compared to the previous version. In addition, the introduction of digital marketing strategies supports significant market expansion. This study confirms that packaging education is an effective strategy in building MSME competitiveness in the digital era. These findings recommend the integration of design education and visual marketing in young entrepreneur empowerment programs in a sustainable manner.